IMPLEMENTASI MODEL PROBLEM BASED LEARNING PADA PEMBELAJARAN PENDIDIKAN PANCASILA DI KELAS V SEKOLAH DASAR - Zaitun; Linda Zakiah; Yurniwati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the implementation of the Problem Based Learning (PBL) model in Pancasila Education learning with the material "Mutual Cooperation in Diversity" in class V SDN Guntur 01 South Jakarta. The data collection techniques used were observation, interviews, and documentation. The collected data were analyzed qualitatively according to the Milles and Hubberman model. The results of the study showed that: (1) The implementation of the PBL model in the Pendidikan Pancasila subject in class V SDN Guntur 01 was able to create a conducive learning environment and the investigation process was active and the learning resources used by students were the internet so that students could investigate problems by looking for relevant information. (2) Classically, students' ability to solve problems after learning with the PBL model can be qualified as good.